Causality Study of Drunk Driver Traffic Violations on Road Safety - Sukmawati, Adik; Farid, Achmad Miftah (DiH: Jurnal Ilmu Hukum, 2025)
The purpose of this study is to explore: (1) the causality and impact of traffic violations by drivers under the influence of alcohol in the Wonogiri District Police area; and (2) the implementation of law enforcement against such traffic violations in the same area. The primary focus of this study is to delve deeper into the causality of traffic violations caused by impaired driving due to alcohol, as well as to evaluate the effectiveness of law enforcement measures applied by the police in addressing these violations. The research method used to support this research is juridical empirical, focusing on traffic violations committed by drunk drivers in the Wonogiri District Police jurisdiction, employing a scientific approach and case study method. The results of this study indicate that alcohol consumption impairs driving concentration and increases the risk of accidents due to impaired visual perception, motor skills, heightened adrenaline, and poor road conditions. In 2024, three accidents were reported to be caused by drunk drivers, highlighting the urgent need for stricter enforcement and increased awareness campaigns. While the Wonogiri District Police enforce traffic regulations, challenges like low public awareness, technical constraints, and corruption persist. Policy recommendations include tightening regulations, improving education programs, and implementing more effective measures.